Caracterização da propagação radioelétrica sobre terrenos irregulares utilizando equações integrais no domínio do tempo - Ruã Luz Barbosa (2018)
In this work it is proposed a formulation to predict the propagation of an electromagnetic wave over a smoothly irregular terrain using the Electric Field Integral Equation in the time domain (TD-EFIE). It is proposed a formulation for near graze incidence of a vertical polarized electromagnetic wave. Given the near graze incidence, the terrain can be treated as a perfect magnetic conductor for the considered polarization and the equivalence principle can be used to find the equivalent magnetic current at the surface using the Method of Moments and the scattered field can then be calculated from the currents. With the terrain being smooth, the backscattering can be neglected and the current at the surface can be calculated recursively, reducing the computational cost. The results found using the TD-EFIE were compared with the ones obtained from previous works using the time-domain Magnetic Field Integral Equation (TD-MFIE) and the time-domain Uniform Theory of Diffraction (TD-UTD). The three methods showed similar results, with only the TD-UTD differing from the others when the problem presents a double diffraction and diffraction in edges with an internal angle greater than 180°. The results from the TD-EFIE also agreed with the ones obtained after applying the inverse Fourier transform in the results obtained from the Electric Field Integral Equation in the frequency domain (FD-EFIE)